National transportation policy : a study of studies - Levine, Harvey A. (Lexington, Massachusetts : Lexington Books, 1978)
The book includes a historical analysis of research on national transportation policy, an evaluation of such research, the linkage of policy research to policy formulation, and suggestions for making future research less wasteful and more relevant.
Includes bibliographical references.
ne 29/06/2018
Loans
Keywords: Transportation and state; Transportation; United States